Reasons for non-evacuation and shelter-seeking behaviour of local population following cyclone warnings along the Bangladesh coast - Edris Alam, PhD (Progress in Disaster Science, 2024)
Bangladesh has successfully reduced the number of deaths caused by tropical cyclones associated with storm surges in its territory. The factors responsible for this success include significant improvements in satellite-based cyclone detection, early warning systems, and emergency evacuation. However, during such events, some residents prefer to not evacuate the region. Based on the first-hand data generated through in-depth interviews, participant observations, focus group discussions with residents aged over 59 years, field visits, and investigations, in this study, we provide information on the shelter-seeking places in Bangladesh during the latest cyclones and analyse the reasons why some residents do not evacuate the affected regions post cyclone warning. The findings suggest that in Bangladesh, community trust in warnings increased from 56% during the 1991 Cyclone Gorky to 96% during the 2020 Cyclone Amphan. We identified 33 reasons for the preference of the population in Bangladesh living along the coast to not move to a cyclone shelter during emergencies; these reasons can be subdivided into six categories: 1) resilient housing, or the residents are living adjacent to strong buildings; 2) reasons associated with public cyclone shelters; 3) to protect livelihoods, properties, and personal belongings; 4) transportation problems and practical issues during the warning period; 5) interrelated community beliefs and perceptions; and 6) reasons directly associated with cyclone warnings. We identified the foundational reasons for the non-evacuation behaviour of the residents and analysed why they preferred to remain home or take shelter in adjacent strong building infrastructures. Notably, our study provides valuable insights into the factors that affect effective evacuation planning and cyclone disaster risk management along the Bangladesh coast.